Preparation and Characterization of Solid Electrolyte Doped With Carbon Nanotubes and its Preliminary Application in NO2 Gas Sensors - Luo, Rubai; Li, Qiqi; Du, Bin; Zhou, Shisheng; Chen, Yuheng (Frontiers in Materials, 2019)
In this paper, a solid polymer electrolyte doped with carbon nanotubes is used as a gas sensing material for a NO2 gas sensor. The electrolytes, consisted of the ionic liquids and carbon nanotubes, which were immobilized in a poly(vinylidene fluoride) (PVDF) matrix. The solid polymer electrolyte membrane was characterized by SEM, XPS and FTIR. The experimental results show that when the solid polymer electrolyte is applied to the NO2 gas sensor, the solid polymer electrolyte after adding an appropriate amount of carbon nanotubes has higher gas sensitivity than the solid polymer electrolyte containing no carbon nanotubes. When the mass ratio of polyvinylidene fluoride, NMP, ionic liquid and carbon nanotube is 1:4:1:0.08, solid polymer electrolytes have good gas sensitivity.